Controlled Growth of Hybrid Halide Perovskites by Crown Ether Complexation for Perovskite Solar Cells. Issue 4 (14th March 2023) - Ju Kim, Sun; Kumar Chitumalla, Ramesh; Kim, Jong‐Min; Jang, Joonkyung; Oh, Jin‐Woo; Milić, Jovana V.; Seo, Ji‐Youn
Abstract: Host‐guest complexation has demonstrated potential for controlling hybrid organic‐inorganic metal halide perovskite materials. In particular, crown ethers have been used due to their capacity to interact with metal cations ( e. g ., Pb 2+ ) and small organic cations ( e. g ., methylammonium (MA)), which can affect hybrid perovskite materials and their solar cells. However, this strategy has been underexploited in perovskite photovoltaics, and the underlying mechanisms are not well understood. In this study, we investigate the influence of 15‐crown‐5 (15C5 ) and its benzannulated derivative (benzo‐15‐crown‐5, B15C5 ), as well as amino‐functionalized analogues (15‐crown‐5)‐2‐methylamine, 2A‐15C5, and 4′‐aminobenzo‐15‐crown‐5, 4A‐B15C5, on MAPbI3 perovskite crystallization and inverted solar cell performance. We demonstrate the propensity of crown ether modulators to interact with Pb 2+ cations at the perovskite interface by density functional theory calculations. This has been shown to facilitate oriented crystal growth and homogeneous film formation, as revealed by X‐ray diffraction analysis complemented by scanning electron microscopy. As a result, we demonstrate an increase in the power conversion efficiency of the solar cells of interest to advancing hybrid photovoltaics. Abstract :